Desiminasi Teknologi Capasitiv Sensor dan Arduino Uno dalam Pembuatan Voicing Poster untuk Peningkatan Pemahaman Sex Education bagi Anak Sekolah Dasar - Sutriyani, Wulan; Wiranti, Dwiana Asih; Wahyusari, Retno; Aprilia, Dyah Ayu Safitri; Mahdum, Esa Adistiya Fajarwati; Subkan, Muhamad Nur; Maziyah, Hilda Nur (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
In the current millennial era, cases of sexual violence in Indonesia continue to increase, making it necessary to provide sex education to children. The partner school in this research is the teacher working group (KKG) of Dabin IV SD Nakula Sadewa cluster in Bangsri sub-district, Jepara district, which consists of 9 elementary schools. They face issues with some elementary school children making jokes that lead to pornographic remarks or engaging in verbal and physical bullying. The aim of this community service program (PKM) is to enhance students' understanding of sex education, improve teachers' ability to master sex education material, and increase teachers' ability to innovate in creating learning media based on Capacitive Sensor technology and Arduino Uno. This research method is carried out in 5 stages: socialization, training, technology application, mentoring, and sustainability. As a result, the partners can improve their competence in developing innovative capacitive sensor technology learning media for elementary school children. From the implementation of this community service activity, the use of capacitive sensor technology-based learning media with Arduino Uno successfully addressed the problems faced by the partners.